Uji Statistik Hipotesis Rata-Rata Durasi Tidur Kelompok di Bawah Standar 7 Jam - Aubin Tri Hariyana; Rafi Ahmad Mifta Hudin; Wahyu Satriyo; Perani Rosyani (CV. Multi Kreasi Media, 2026)
Adequate sleep is a vital necessity for physical and mental health. This study aims to test the hypothesis of whether the average sleep duration in a mixed group (students and workers) is less than the recommended limit of 7 hours. Using a quantitative method with the One-Sample T-Test statistical test, this study analyzed data from 21 respondents collected through online questionnaires. Descriptive analysis results showed the average sleep duration of respondents was 6.64 hours with a standard deviation of 1.18. However, the t-test result showed a t_count value of -1.40, which was not significant at the 0.05 level. Therefore, statistically, there is not enough evidence to state that the population average is less than 7 hours. Additionally, a pattern of relationship was found between high gadget usage and anxiety with short sleep duration.